Molecular Genetics Unveiled Unknown Family Relationships and Hybrids in an Ex-Situ Colony of African Penguins (Spheniscus demersus). (13th July 2018) - Modesto, Paola; Biolatti, Cristina; Favaro, Livio; Colussi, Silvia; Peletto, Simone; Piga, Sara; Riina, Maria Vittoria; Pessani, Daniela; Trincas, Egle; Isaja, Valentina; Acutis, Pier Luigi
Abstract: Genealogical relationships among colony members, inbreeding status, and presence of hybrids are crucial data that can assist zoo curators in captive colony management and decision-making on relocation for reproduction. This study employed molecular markers to study a large colony ( n = 56) of African Penguin hosted in an Italian biopark. A panel of 15 STRs (single tandem repeats) was selected, and genotype data were analyzed using COLONY software to determine parentage relationships and compare the existing studbook information to a pedigree built from genetic analyses. The existence of extra-pair mating and the presence of hybrids were investigated: discrepancies in kinship relationships emerged following molecular parentage analysis and 10 unknown genetic relationships were revealed. Infidelity of one member of the pair was observed in 6 cases and extra-pair copulation was assessed by genetic analysis in 2 episodes. One member of the colony was found to be a hybrid ( S. demersus × S. humboldti ); his progeny, derived by extra-pair copulation, was traced. Three other hidden hybrids were discovered and assessed using the identified candidate private alleles. Overall, our results demonstrate that molecular methods to confirm parentage and analyze relatedness among colony members are a valuable tool to complement studbook-based genetic management of African penguin captive populations. Because a variety of behavioral dynamics (e.g., extra-pair mating) can make observations ineffective in some species and because molecular markers outperform studbook in identifying the presence of hybrids, reliance on studbook information alone is not recommended.